Educational Programs For Financial Planning in Jogahan Village, Kulon Progo, Yogyakarta - Dimas Bagus Wiranatakusuma (Departement of Mathematics Education, 2023)
Financial education is a strategy for mitigating the effects of unexpected financial crises. Planning is essential not only for organizations, but also for people and households. However, when compared to financial planning in practice, such as investment or saving recommendations, study focusing on financial education is uncommon. In our situation, for example, residents of Jogahan village are illiterate and admit to lacking financial planning expertise. As a result, the purpose of this study is to evaluate the efficacy of a month-long financial education program aimed primarily at children, youth, and society in general. According to the results, the programs achieve an 80% degree of success from the intended targets. The programs helped them improve their financial literacy, which included financial planning. However, this application did not teach them using an algorithm that can indicate the optimal composition of assets accumulated in order to maintain their life sustainability. Financial education, in the long term, contributes to a more sustainable existence as well as a more resilient economic society.